Polylactic acid two-component composite fiber and degradable absorption core body prepared from polylactic acid two-component composite fiber
Through the multi-layer structure design of polylactic acid two-component composite fiber and highly absorbent resin, the problems of small absorption, easy to damp and non-degradable in the existing absorbent layer materials are solved, and the absorption effect of high efficiency, degradability and natural antibacteriality is achieved .
Patent Information
- Application Number
- CN202411410053.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The absorbent layer materials of existing disposable sanitary materials have problems such as small absorption, easy to moisture, bacterial growth, and non-degradable. The utilization rate of high-water-absorbing resin is not high, and non-degradable hot melt adhesive is required for fixation.
Polylactic acid two-component composite fibers are used to prepare cross-shaped cross-section high and low melting point polylactic fibers through drying, melt extrusion and spinning processes, and combined with high water-absorbing resin to form a multi-layer structure of degradable and absorbent core, using fibers Wet conductivity and high curlability fix high water-absorbing resin to improve absorption capacity.
It achieves high absorption, biodegradability, gradient absorption effect and natural antibacterial properties, reduces the use of high-water-absorbing resin, reduces production costs, and maintains the dryness and efficient water-absorbing properties of the absorbent material.
Smart Images

Figure CN119287536A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polylactic acid two-component composite fiber and a degradable absorbent core prepared therefrom, belonging to the technical field of polylactic acid fibers and products thereof. Background Art
[0002] There are generally three types of absorbent layer materials used in disposable sanitary materials, namely pure wood pulp absorbent material, wood pulp and super absorbent resin mixed absorbent material, and 100% super absorbent resin + fluffy cotton absorbent material. Although the pure wood pulp absorbent material is 100% natural material and 100% degradable, it has a small absorption capacity, and the wood pulp will be very moist after absorption saturation, which is easy to breed bacteria, so it can only be used in ordinary sanitary napkins; the second type of wood pulp and super absorbent resin mixed absorbent material uses wood pulp fiber as a drainage material, which can quickly drain the liquid to the surrounding super absorbent resin, but there is also a problem that when the hands are saturated, the absorbent material will be very moist due to the presence of a large amount of wood pulp. In addition, hot melt adhesive needs to be sprayed to fix the wood pulp and super absorbent resin, which will hinder the further improvement of the absorption capacity, so the occasions of use will also be limited. , this absorbent material cannot be degraded due to the presence of super absorbent resin; the third type is 100% super absorbent resin + fluffy cotton, which uses fluffy cotton as an isolation layer to accommodate more super absorbent resin, but the fluffy cotton only plays an isolating role and cannot accommodate and cover the super absorbent resin, and cannot provide sufficient swelling space for the super absorbent resin. Therefore, after absorption saturation, the super absorbent resin is very likely to produce local blockage, hindering further absorption of liquid, so the utilization rate of the super absorbent resin is not high. In addition, a large amount of hot melt adhesive needs to be sprayed to fix the fluffy cotton and the super absorbent resin, which further hinders the full utilization of the super absorbent resin. The fluffy cotton used in this absorbent material is 100% PE / PP and PE / PET fiber, and the super absorbent resin is an acrylic material, both of which are non-degradable.
[0003] How to prepare a degradable polylactic acid two-component composite fiber and a degradable absorbent core prepared therefrom has become a problem to be solved. Summary of the invention
[0004] One of the purposes of the present invention is to provide a polylactic acid two-component composite fiber with a cross-shaped cross section and good moisture conduction effect.
[0005] Another object of the present invention is to provide a degradable absorbent core having both degradability and high absorbency.
[0006] To solve the above technical problems, the purpose of the present invention is achieved as follows:
[0007] The polylactic acid two-component composite fiber of the present invention comprises a core with a cross-shaped cross section and a sheath with a cross-shaped cross section wrapped outside the core layer; the core is high-melting-point polylactic acid, and the sheath is low-melting-point polylactic acid;
[0008] The preparation process of the polylactic acid two-component composite fiber is as follows:
[0009] 1) First, the high melting point polylactic acid slices and the low melting point polylactic acid slices are dried by a drying device until the water content of the high melting point polylactic acid slices and the low melting point polylactic acid slices is 0.008-0.015%;
[0010] 2) The dried high-melting-point polylactic acid slices and low-melting-point polylactic acid slices are respectively sent to the twin screws of a composite twin-screw spinning machine for melt extrusion; the screw extrusion temperature of the low-melting-point polylactic acid component is 170-190° C., and the screw extrusion temperature of the high-melting-point polylactic acid component is 200-230° C.; after being metered and filtered, they are sent to the composite spinning assembly of the spinning machine;
[0011] The spinning parameters are as follows: the spinning temperature is controlled at 215-245°C, the spinning speed is controlled at 600-1000m / min, the side blowing temperature is controlled at 20-24°C, the side blowing speed is controlled at 0.8-1.2m / s, the pre-drafting multiple is controlled at 1.3-1.8, and then after oiling treatment, a secondary oiling process is adopted; the first oiling adopts an oil bath oiling method, and the oiling rate is controlled at 0.18-0.25%, and then enters the stretching process, the stretching multiple is controlled at 1.5-2.0, and then tensile heat setting is carried out, the heat setting temperature is controlled at 55-65°C, and then the second oiling is carried out, the oiling is carried out by an oil tanker or a spraying method, the oiling rate is controlled at 0.1-0.2%, and then enters the secondary heat setting method, the temperature is controlled at 90-110°C, and then winding and cutting are performed to obtain a high-low melting point two-component polylactic acid composite fiber with a cross-shaped cross section.
[0012] On the basis of the above scheme and as a preferred scheme of the above scheme: the drying equipment is a drum drying equipment; the low melting point polylactic acid component has a melt index of 18g / 10min; the high melting point polylactic acid component has a melt index of 23g / 10min.
[0013] On the basis of the above scheme and as a preferred scheme of the above scheme: the fiber fineness of the polylactic acid two-component composite fiber is 1.5-6dtex, the number of curls is 2-5 / 2.5mm, and the curl angle is 80-100 degrees; and the cross aspect ratio of the polylactic acid two-component composite fiber is 3-7:1, and the fiber length is 3-20mm.
[0014] On the basis of the above scheme and as a preferred scheme of the above scheme: the volume ratio of the high melting point polylactic acid slices to the low melting point polylactic acid component is 60-80:20-40.
[0015] The present invention also relates to a degradable absorbent core, comprising the polylactic acid two-component composite fiber;
[0016] The degradable absorbent core comprises a surface layer, a middle layer and a bottom layer; the surface layer and the bottom layer are single-component polylactic acid fiber non-woven fabrics; the middle layer comprises polylactic acid two-component composite fibers with a cross section, highly curled and highly elastic polylactic acid two-component fibers and highly absorbent resin.
[0017] On the basis of the above scheme and as a preferred scheme of the above scheme: the high-curl and high-elastic polylactic acid two-component fiber is in parallel type, including a low melting point component and a high viscosity component, the melt index of the low viscosity component is 23g / 10min, and the melt index of the high viscosity component is 6g / 10min; the fiber fineness of the high-curl and high-elastic polylactic acid two-component fiber is 1.5-6dtex, the number of curls is 8-12 / 2.5mm, and the fiber length is 10-25mm.
[0018] On the basis of the above scheme and as a preferred scheme of the above scheme: the preparation process of the intermediate layer is:
[0019] 1) Fiber mixing: mixing the cross-sectioned polylactic acid two-component composite fiber and the high-curl high-elasticity polylactic acid two-component fiber to form a fiber mixture;
[0020] 2) Mixing: Mixing the fiber mixture with the super absorbent resin to prepare a first fiber resin mixture, a second fiber resin mixture and a third fiber resin mixture;
[0021] The ratio of fiber mixture to super absorbent resin in the first fiber resin mixture is 0-2:8-10, wherein the particle size of the super absorbent resin used is 100-120 mesh;
[0022] The ratio of fiber mixture to super absorbent resin in the second fiber resin mixture is 4-6:4-6, wherein the particle size of the super absorbent resin used is 80-100 mesh;
[0023] The ratio of fiber mixture to super absorbent resin in the third fiber resin mixture is 7-9:1-3, wherein the particle size of the super absorbent resin used is 40-70 meshes.
[0024] On the basis of the above scheme and as a preferred scheme of the above scheme: the mixing ratio of the polylactic acid two-component composite fiber and the high-curl high-elasticity polylactic acid two-component fiber is 50-70:50-30.
[0025] On the basis of the above scheme and as a preferred scheme of the above scheme: the preparation process of the degradable absorbent core uses a non-woven fabric compounding machine with three spray heads, and the specific preparation process is as follows:
[0026] 1) Preparation before compounding: adjust the height between the first spray head and the compound machine table to 10-13 cm, adjust the height between the second spray head and the compound machine table to 12-14 cm, and adjust the height between the third spray head and the compound machine table to 13-15 cm;
[0027] 2) unwinding the polylactic acid spunbonded nonwoven fabric used for the bottom layer and sending it to a nonwoven fabric laminating machine for lamination, wherein the polylactic acid spunbonded nonwoven fabric with a specification of 15-20 g / m2 is selected;
[0028] 3) When the polylactic acid spunbond nonwoven fabric runs to the first powder spraying head, the first powder spraying head sprays the first fiber resin mixture thereon, the spraying amount is 120-180 g / m2, and the vibration frequency of the first spraying head during spraying is 20-30 Hz;
[0029] 4) When the polylactic acid spunbonded nonwoven fabric runs to the second powder sprinkling head, the second powder sprinkling head sprays the second fiber resin mixture thereon, the spraying amount is 60-100 g / m2, and the vibration frequency of the second spraying head during spraying is 28-38 Hz;
[0030] 5) When the polylactic acid spunbonded nonwoven fabric runs to the third powder spraying head, the third powder spraying head sprays the third fiber resin mixture thereon, the spraying amount is 40-70 g / m2, and the vibration frequency of the third spraying head during spraying is 35-45 Hz;
[0031] 6) unwinding the polylactic acid hot air nonwoven fabric used for the surface layer, and superimposing it on the sprayed third fiber resin mixture, so that the polylactic acid spunbond nonwoven fabric is at the bottom layer, the middle layer is a three-layer cross-shaped polylactic acid bicomponent fiber + a high-curl high-elasticity polylactic acid bicomponent fiber superabsorbent resin mixture, and the upper layer is a five-layer composite structure of polylactic acid hot air nonwoven fabric;
[0032] The composite structure is then put into an oven for shaping. The hot air penetration temperature in the oven is 115-140°C and the running speed is 15-20 m / min. After exiting the oven, a five-layer composite absorbent material is obtained with a gram weight of 300-460 g / m2.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. Good moisture absorption and moisture conductivity.
[0035] Polylactic acid fiber is a man-made natural fiber from plants. The surface of polylactic acid fiber is weakly acidic and has natural antibacterial properties. The fiber has good moisture conductivity, low moisture regain, and good surface dryness. What's more special is that polylactic acid fiber is 100% biodegradable, so it will definitely become the future development direction of disposable sanitary materials.
[0036] The present invention uses a reasonable spinning process selection of the cross-shaped two-component polylactic acid fiber, and particularly adopts a two-step oiling process to give the cross-shaped two-component polylactic acid fiber better hygroscopicity, moisture conductivity and good dispersibility, so that the cross-shaped two-component polylactic acid fiber can quickly absorb liquid and transfer the liquid to the surrounding super absorbent resin. In addition, the protruding blades of the cross-shaped polylactic acid fiber can wrap around the super absorbent resin in a semi-elliptical form, fix the super absorbent resin, and isolate the super absorbent resins from each other, provide a swelling space for the super absorbent resin, and avoid too much super absorbent resin crowding together and causing blockage due to absorption saturation. On the other hand, the composite absorbent material of the present invention does not use hot melt adhesive to fix the super absorbent resin, but wraps the super absorbent resin through the blades of the cross-shaped fiber and the highly curled elliptical shape, thereby increasing the specific surface area of the super absorbent resin exposed to the outside, providing more swelling space for better absorption of the super absorbent resin, improving the absorption capacity of the core and the ability to lock liquid, reducing the use of the super absorbent resin, and thus reducing production costs.
[0037] 2. Biodegradable.
[0038] The composite absorbent material prepared by the present invention has a polylactic acid spunbond non-woven fabric as a bottom layer, a middle layer of a cross-shaped polylactic acid two-component composite fiber + a mixture of a high-curl high-elastic polylactic acid two-component fiber and a super absorbent resin, and a surface layer of a porous polylactic acid hot air non-woven fabric. The polylactic acid in the material used is a 100% biodegradable fiber, and the super absorbent resin is the biodegradable absorbent resin BC706 of Formosa Plastics Corporation, and its biodegradability is 66% (180 days). According to the evaluation standards of EN 13432 and GB / T 20197, the composting degradation rate or biodegradation rate of bio-based care products is ≥60%, which meets the degradation standard requirements.
[0039] 3. Gradient absorption effect.
[0040] The absorbent material of the present invention adopts a five-layer structure, wherein the cross-shaped polylactic acid two-component composite fiber used in the middle layer has excellent moisture absorption and moisture conductivity due to its unique groove effect, and the high-curl high-elasticity polylactic acid two-component fiber is used to fix and wrap the super absorbent resin due to its unique three-dimensional curling and elasticity, thereby eliminating the use of hot melt adhesive in the conventional core to fix the super absorbent resin, thereby reducing the absorption capacity of the super absorbent resin. Finally, the gradient absorption effect is achieved by the different mixing ratios of the cross-shaped polylactic acid two-component composite fiber + the high-curl high-elasticity polylactic acid two-component fiber and the super absorbent resin and the reasonable selection of the mesh number of the super absorbent resin. The top layer of the three-layer material uses a high proportion of polylactic acid fibers and a high-absorbent resin with a large mesh size, which plays a role in preliminary absorption and drainage of liquids; the second layer uses a medium proportion of polylactic acid fibers and a high-absorbent resin with a medium mesh size, which mainly plays a role in absorption, and also has a certain degree of drainage of liquids; the third layer uses a very low proportion of polylactic acid fibers and a high-absorbent resin with a small mesh size, which mainly plays a role in absorption, and the cross-shaped polylactic acid two-component composite fiber only plays a role in fixing and slightly draining the high-absorbent resin. Such a gradient absorption effect can quickly drain the liquid to be absorbed by the high-absorbent resin, so that it will not agglomerate and clog after absorption saturation, with high utilization rate and good absorption capacity. In addition, since the moisture regain of polylactic acid fibers is only 0.4-0.6%, the absorbent material can maintain good dryness while absorbing water efficiently.
[0041] 4. Natural weak acidity and antibacterial properties
[0042] The absorbent material of the present invention adopts a five-layer structure, wherein the surface layer and the bottom layer are both non-woven fabrics composed of polylactic acid fibers, and the middle layer uses cross-shaped polylactic acid two-component composite fibers. Since the surface of the polylactic acid fiber is weakly acidic, which is consistent with the pH value of human skin, a weakly acidic microenvironment is created during use. In particular, since the layer in the core body is the polylactic acid hot air non-woven fabric, the bottom layer is the polylactic acid spunbonded non-woven fabric, and a large amount of cross-shaped polylactic acid two-component composite fibers are used in the middle layer, it has a good effect on absorbing odors, and the natural antibacterial and deodorizing properties created further increase the health and comfort of users. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 It is a schematic diagram of the cross-sectional structure of the polylactic acid two-component composite fiber involved in the present invention;
[0044] Figure 2 is a diagram showing a cross section of a polylactic acid bicomponent composite fiber according to the present invention;
[0045] Figure 3 is a longitudinal diagram of the polylactic acid two-component composite fiber involved in the present invention;
[0046] Figure 4It is a cross-sectional view of a parallel type highly curled and highly elastic polylactic acid bicomponent fiber;
[0047] Figure 5 This is the appearance of the parallel type highly curled and highly elastic polylactic acid bicomponent fiber;
[0048] Figure 6 It is a schematic structural diagram of the absorbable core involved in the present invention;
[0049] Figure 7 It is a side view of the absorbable core involved in the present invention.
[0050] The markings in the figure are as follows: 1-core; 2-skin; 10-surface layer; 20-middle layer; 30-bottom layer; 21-first fiber resin mixture; 22-second fiber resin mixture; 23-third fiber resin mixture. DETAILED DESCRIPTION
[0051] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.
[0052] Embodiment 1
[0053] The polylactic acid two-component composite fiber involved in this embodiment is as follows: Figure 1 and Figure 2 As shown, it includes a core with a cross-shaped cross section and a skin coated on the outside of the core layer and with a cross-shaped cross section; the core is made of high-melting-point polylactic acid, and the skin is made of low-melting-point polylactic acid.
[0054] The preparation process of the polylactic acid two-component composite fiber is as follows:
[0055] First, the high melting point polylactic acid chips are dried at 100°C for 4-6 hours using a drum drying device, and the low melting point polylactic acid chips are dried at 40°C for 22-24 hours using a drum drying device to remove moisture, increase the softening point, and avoid oxidation and degradation during the spinning process, thereby reducing the strength of the polylactic acid composite fiber. The low melting point polylactic acid component comes from, The polylactic acid resin model is LX930, with a melt index of 18g / 10min (210℃ / 2.16kg); the high melting point polylactic acid component comes from, The polylactic acid resin model LX130 has a melt index of 23g / 10min (210°C / 2.16kg), which makes the water content of the high and low melting point polylactic acid chips reach 0.008-0.015%.
[0056] The high and low melting point polylactic acid slices after drying are respectively sent to the twin screws of the composite twin-screw spinning machine for melt extrusion, wherein the screw extrusion temperature of the low melting point polylactic acid component is 170°C, and the screw extrusion temperature of the high melting point polylactic acid component is 200°C; after metering and filtration, they are sent to the composite spinning assembly of the spinning machine, and the volume ratio of the high and low melting point polylactic acid components is 60:40. Due to the large difference in melting points of the high and low melting point polylactic acid components, in order to avoid the phenomenon of broken ends and injected ends during the spinning process, the successful spinning parameters are: the spinning temperature is controlled at (215°C), the spinning speed is controlled at 1000m / min, and the side The blowing temperature is controlled at 20°C, the side blowing speed is controlled at 0.8m / s, the pre-drawing multiple is controlled at (1.3), and then after oiling treatment, a secondary oiling process is adopted. The first oiling adopts the oil bath oiling method, and the short fiber oil agent of Japan Takemoto Oil Co., Ltd., model 6214-TS, is used. The oiling rate is controlled at 0.18%. Then it enters the stretching process, and the stretching multiple is controlled at (1.5). Then, tensile heat setting is carried out, and the heat setting temperature is controlled at (55°C). Then, the secondary oiling is carried out, and the oiling is carried out by oil tanker or spraying. The multiple hydrophilic oil agent Lurol of Goulston Company is used. PP-14160, the oiling rate is controlled at 0.1%, enters the secondary heat setting, the temperature is controlled at (90°C), and then it is wound and cut to obtain a high and low melting point two-component polylactic acid composite fiber with a cross-shaped cross section. The fiber fineness is 1.5dtex, the number of curls is 5 / 2.5mm, the curl angle is 100, the cross aspect ratio of the composite fiber is 7:1, and the fiber length is 10mm.
[0057] The degradable absorbent core involved in this embodiment includes the polylactic acid two-component composite fiber; the degradable absorbent core includes a surface layer 10, a middle layer 20 and a bottom layer 30; the surface layer 10 and the bottom layer 30 are single-component polylactic acid fiber non-woven fabrics; the middle layer includes polylactic acid two-component composite fibers with a cross cross-section, highly curled and highly elastic polylactic acid two-component fibers and a highly absorbent resin.
[0058] In the process of preparing the degradable absorbent core, the materials used are: prepared polylactic acid bicomponent composite fiber with a cross-shaped cross section, high-curl high-elastic polylactic acid bicomponent fiber and polylactic acid fiber non-woven fabric, among which the polylactic acid fiber non-woven fabric is preferably polylactic acid spunbond non-woven fabric. The high-curl polylactic acid bicomponent fiber is a degradable high-curl fiber with a parallel cross section developed by Suzhou Jinquan New Materials Co., Ltd., in which one of the low-viscosity components is Polylactic acid resin model LX530, melt index is 23g / 10min (210℃ / 2.16kg); high viscosity component polylactic acid comes from The PLA resin model is LX175, and the melt index is 6g / 10min (210℃ / 2.16kg). The high-curl PLA bicomponent fiber has a fineness of 6dtex, a number of crimps of 12 / 2.5mm, and a fiber length of 25mm.
[0059] Fiber mixing: A three-dimensional motion mixer is used to mix the cross-type polylactic acid bicomponent fiber and the high-curl high-elasticity polylactic acid bicomponent fiber, with the ratio of cross-type polylactic acid bicomponent fiber to high-curl high-elasticity polylactic acid bicomponent fiber being 50:50.
[0060] Mixing: The fiber mixture and the super absorbent resin are mixed in different weight ratios to prepare a first fiber resin mixture 21, a second fiber resin mixture 22 and a third fiber resin mixture 3, which are respectively:
[0061] 1) Cross-shaped polylactic acid two-component fiber + high-curl high-elastic polylactic acid two-component fiber: super absorbent resin: 0:10, wherein the particle size of the super absorbent resin used is 100 mesh; the speed of the mixer during mixing is 10rpm, the mixing time is 30 minutes, and then the mixed material is poured out for standby use, i.e. the first fiber resin mixture. The mixer adopts a three-dimensional motion mixer produced by Jiangsu Guibao, model SBH300.
[0062] 2) Cross-shaped polylactic acid two-component fiber + high-curl high-elastic polylactic acid two-component fiber: super absorbent resin: 4:6, where the particle size of the super absorbent resin used is 100 mesh. The speed of the mixer during mixing is 10rpm, the mixing time is 30 minutes, and then the mixed material is poured out for use, that is, the second fiber resin mixture. The mixer uses a three-dimensional motion mixer produced by Jiangsu Guibao, model SBH300.
[0063] 3) Cross-shaped polylactic acid two-component fiber + high-curl high-elastic polylactic acid two-component fiber: super absorbent resin: 7:3, where the particle size of the super absorbent resin used is 40 mesh. The speed of the mixer during mixing is 12rpm, the mixing time is 35 minutes, and then the mixed material is poured out for use, that is, the third fiber resin mixture. The mixer uses a three-dimensional motion mixer produced by Jiangsu Guibao, model SBH300.
[0064] In the process of preparing the degradable absorbent core, a non-woven fabric compounding machine with three spray heads, produced by Jiangsu Gaoqi Machinery Co., Ltd., model GQ-1600, was selected. The preparation process of the degradable absorbent core is as follows:
[0065] 1) Preparation before compounding: adjust the height between the first spray head and the compound machine table to 10 cm, adjust the height between the second spray head and the compound machine table to 12 cm, and adjust the height between the third spray head and the compound machine table to 13 cm.
[0066] 2) Unwind the polylactic acid spunbond nonwoven fabric and send it to the nonwoven fabric laminating machine for lamination. The selected specification is 15g / m 2 Polylactic acid spunbond nonwoven fabric.
[0067] 3) When the polylactic acid spunbond nonwoven fabric runs to the first powder sprinkling head, the first powder sprinkling head sprays a mixture of cross-shaped polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber and super absorbent resin on it. The selected ratio is cross-shaped polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber: super absorbent resin: 0:10, that is, the first fiber resin mixture, the spraying amount is 180 g / m2, and the vibration frequency of the first spraying head during spraying is 20 Hz.
[0068] 4) When the polylactic acid spunbond nonwoven fabric runs to the second powder sprinkling head, the second powder sprinkling head sprays a mixture of cross-shaped polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber and super absorbent resin on it. The selected ratio is cross-shaped polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber: super absorbent resin: 4:6, that is, the second fiber resin mixture, the spraying amount is 100 g / m2, and the vibration frequency of the second spraying head during spraying is 28 Hz.
[0069] 5) When the polylactic acid spunbond nonwoven fabric runs to the third powder sprinkling head, the third powder sprinkling head sprays a mixture of cross-type polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber and super absorbent resin on it. The selected ratio is cross-type polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber: super absorbent resin: 7:3, that is, the third fiber resin mixture, the spraying amount is 70 g / m2, and the vibration frequency of the third spraying head during spraying is 35 Hz.
[0070] 6) Polylactic acid hot air nonwoven fabric is unwound (polylactic acid hot air nonwoven fabric specification is 15g / m2), superimposed on the top layer of cross-shaped polylactic acid bicomponent fiber + high curl high elastic polylactic acid bicomponent fiber and super absorbent resin mixture, forming a polylactic acid spunbond nonwoven fabric at the bottom layer, three layers of cross-shaped polylactic acid bicomponent fiber + high curl high elastic polylactic acid bicomponent fiber and super absorbent resin mixture in the middle, and a five-layer composite structure of polylactic acid hot air nonwoven fabric on the top layer. The composite structure is then put into the oven for shaping treatment. The hot air penetration temperature in the oven is 115°C, and the operating speed is 15 meters / minute. After leaving the oven, a five-layer composite absorbent material is obtained with a gram weight of 410 grams / square meter. The core can be used for the absorption layer of disposable sanitary materials such as diapers, sanitary napkins and nursing pads.
[0071] Embodiment 2
[0072] The polylactic acid two-component composite fiber involved in this embodiment is as follows: Figure 1 and Figure 2As shown, it includes a core with a cross-shaped cross section and a skin coated on the outside of the core layer and with a cross-shaped cross section; the core is made of high-melting-point polylactic acid, and the skin is made of low-melting-point polylactic acid.
[0073] The preparation process of the polylactic acid two-component composite fiber is as follows:
[0074] First, a drum drying device is used to dry the high-melting point polylactic acid chips at 100°C for 4-6 hours, and a drum drying device is used to dry the low-melting point polylactic acid chips at 40°C for 22-24 hours to remove moisture, increase the softening point, and avoid oxidation and degradation during the spinning process, thereby reducing the strength of the polylactic acid composite fiber.
[0075] The low melting point polylactic acid component comes from: The polylactic acid resin model is LX930, with a melt index of 18g / 10min (210℃ / 2.16kg); the high melting point polylactic acid component comes from, The polylactic acid resin model is LX130, and the melt index is 23g / 10min (210°C / 2.16kg), so that the water content of the high and low melting point polylactic acid chips reaches 0.008-0.015%.
[0076] 2) The high and low melting point polylactic acid slices after drying are respectively sent to the twin screws of the composite twin screw spinning machine for melt extrusion, wherein the screw extrusion temperature of the low melting point polylactic acid component is 190°C, and the screw extrusion temperature of the high melting point polylactic acid component is 230°C; after metering and filtration, they are sent to the composite spinning assembly of the spinning machine, and the volume ratio of the high and low melting point polylactic acid components is 80:20. Due to the large difference in melting points of the high and low melting point polylactic acid components, in order to avoid the phenomenon of broken ends and injected ends during the spinning process, the successful spinning parameters are: the spinning temperature is controlled at (245°C), the spinning speed is controlled at 600m / min, and the side The blowing temperature is controlled at 24°C, the side blowing speed is controlled at 1.2m / s, the pre-drawing multiple is controlled at (1.8), and then after oiling treatment, a secondary oiling process is adopted. The first oiling adopts the oil bath oiling method, and the short fiber oil agent of Japan Takemoto Oil Co., Ltd., model 6214-TS, is used. The oiling rate is controlled at 0.25%. Then it enters the stretching process, and the stretching multiple is controlled at (2.0). Then, tensile heat setting is carried out, and the heat setting temperature is controlled at (65°C)°C. Then, the secondary oiling is carried out, and the oiling is carried out by oil tanker or spraying, and the multiple hydrophilic oil agent Lurol of Goulston Company is used. PP-14160, the oiling rate is controlled at 0.2%, enters the secondary heat setting, the temperature is controlled at (110°C), and then it is wound and cut to obtain a high and low melting point two-component polylactic acid composite fiber with a cross-shaped cross-section. The fiber fineness is 5.5dtex, the number of curls is 2 / 2.5mm, the curl angle is 80, the cross aspect ratio of the composite fiber is 3:1, and the fiber length is 2mm.
[0077] The degradable absorbent core involved in this embodiment includes the polylactic acid two-component composite fiber; the degradable absorbent core includes a surface layer 10, a middle layer 20 and a bottom layer 30; the surface layer 10 and the bottom layer 30 are single-component polylactic acid fiber non-woven fabrics; the middle layer includes polylactic acid two-component composite fibers with a cross cross-section, highly curled and highly elastic polylactic acid two-component fibers and a highly absorbent resin.
[0078] In the process of preparing the degradable absorbent core, the materials used are: prepared cross-shaped polylactic acid bicomponent fiber, high-curl and high-elastic polylactic acid bicomponent fiber and polylactic acid fiber non-woven fabric, among which the polylactic acid fiber non-woven fabric is preferably polylactic acid spunbond non-woven fabric. The high-curl polylactic acid bicomponent fiber is a degradable high-curl fiber with a parallel cross-section specially developed by Suzhou Jinquan New Materials Co., Ltd., in which one of the low-viscosity components is Polylactic acid resin model LX530, melt index is 23g / 10min (210℃ / 2.16kg); high viscosity component polylactic acid comes from The polylactic acid resin model is LX175, and the melt index is 6g / 10min (210℃ / 2.16kg). The fineness of the high-curl polylactic acid two-component fiber is 3dtex, the number of crimps is 10 / 2.5mm, and the fiber length is 15mm.
[0079] Fiber mixing: A three-dimensional motion mixer is used to mix the cross-type polylactic acid bicomponent fiber and the high-curl high-elasticity polylactic acid bicomponent fiber, the cross-type polylactic acid bicomponent fiber: the high-curl high-elasticity polylactic acid bicomponent fiber = 60:40.
[0080] Mixing: The fiber mixture and the super absorbent resin are mixed in different weight ratios to prepare a first fiber resin mixture 21, a second fiber resin mixture 22 and a third fiber resin mixture 3, which are respectively:
[0081] 1) Cross-shaped polylactic acid two-component fiber + high-curl high-elastic polylactic acid two-component fiber: super absorbent resin: 2:10, where the particle size of the super absorbent resin used is 120 mesh; the speed of the mixer during mixing is 14rpm, the mixing time is 40 minutes, and then the mixed materials are poured out for use, that is, the first fiber resin mixture. The mixer uses a three-dimensional motion mixer produced by Jiangsu Guibao, model SBH300.
[0082] 2) Cross-shaped polylactic acid two-component fiber + high-curl high-elastic polylactic acid two-component fiber: super absorbent resin: 6:4, where the particle size of the super absorbent resin used is 100 mesh. The speed of the mixer during mixing is 15rpm, the mixing time is 50 minutes, and then the mixed material is poured out for use, that is, the second fiber resin mixture. The mixer uses a three-dimensional motion mixer produced by Jiangsu Guibao, model SBH300.
[0083] 3) Cross-shaped polylactic acid two-component fiber + high-curl high-elastic polylactic acid two-component fiber: super absorbent resin: 9:1, where the particle size of the super absorbent resin used is 70 mesh. The speed of the mixer during mixing is 15rpm, the mixing time is 50 minutes, and then the mixed material is poured out for use, that is, the third fiber resin mixture. The mixer uses a three-dimensional motion mixer produced by Jiangsu Guibao, model SBH300.
[0084] In the process of preparing the degradable absorbent core, a non-woven fabric compounding machine with three spray heads, produced by Jiangsu Gaoqi Machinery Co., Ltd., model GQ-1600, was selected. The preparation process of the degradable absorbent core is as follows:
[0085] 1) Preparation before compounding: adjust the height between the first spray head and the compound machine surface to 13cm, the height between the second spray head and the compound machine surface to 14cm, and the height between the third spray head and the compound machine surface to 15cm.
[0086] 2) Unwind the polylactic acid spunbond nonwoven fabric and send it to a nonwoven fabric laminating machine for lamination. The polylactic acid spunbond nonwoven fabric with a specification of 20 g / m2 is selected.
[0087] 3) When the polylactic acid spunbond nonwoven fabric runs to the first powder sprinkling head, the first powder sprinkling head sprays a mixture of cross-shaped polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber and super absorbent resin on it. The selected ratio is cross-shaped polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber: super absorbent resin: 2:10, that is, the first fiber resin mixture, the spraying amount is 120 g / m2, and the vibration frequency of the first spraying head during spraying is 30 Hz.
[0088] 4) When the polylactic acid spunbond nonwoven fabric runs to the second powder sprinkling head, the second powder sprinkling head sprays it with a mixture of cross-shaped polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber and super absorbent resin. The selected ratio is cross-shaped polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber: super absorbent resin: 6:4, that is, the second fiber resin mixture, the spraying amount is 60 g / m2, and the vibration frequency of the second spraying head during spraying is 38 Hz.
[0089] 5) When the polylactic acid spunbond nonwoven fabric runs to the third powder sprinkling head, the third powder sprinkling head sprays a mixture of cross-type polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber and super absorbent resin on it. The selected ratio is cross-type polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber: super absorbent resin: 9:1, that is, the third fiber resin mixture, the spraying amount is 40 g / m2, and the vibration frequency of the third spraying head during spraying is 45 Hz.
[0090] 6) Polylactic acid hot air nonwoven fabric is unwound (the specification of polylactic acid hot air nonwoven fabric is 20g / m2), and it is superimposed on the top layer of cross-shaped polylactic acid bicomponent fiber + high curl high elastic polylactic acid bicomponent fiber and super absorbent resin mixture to form a polylactic acid spunbond nonwoven fabric at the bottom layer, three layers of cross-shaped polylactic acid bicomponent fiber + high curl high elastic polylactic acid bicomponent fiber and super absorbent resin mixture in the middle, and a five-layer composite structure of polylactic acid hot air nonwoven fabric on the top layer. The composite structure is then put into the oven for shaping treatment. The hot air penetration temperature in the oven is 140°C, and the operating speed is 20 meters / minute. After exiting the oven, a five-layer composite absorbent material is obtained with a gram weight of 260 grams / square meter. The core can be used for the absorption layer of disposable sanitary materials such as diapers, sanitary napkins and nursing pads.
[0091] Embodiment 3
[0092] The polylactic acid two-component composite fiber involved in this embodiment is as follows: Figure 1 and Figure 2 As shown, it includes a core with a cross-shaped cross section and a skin coated on the outside of the core layer and with a cross-shaped cross section; the core is made of high-melting-point polylactic acid, and the skin is made of low-melting-point polylactic acid.
[0093] The preparation process of the polylactic acid two-component composite fiber is as follows:
[0094] 1) First, the high-melting-point polylactic acid chips are dried at 100°C for 4-6 hours using a drum drying device, and the low-melting-point polylactic acid chips are dried at 40°C for 22-24 hours using a drum drying device to remove moisture, increase the softening point, and avoid oxidation and degradation during the spinning process, thereby reducing the strength of the polylactic acid composite fiber.
[0095] The low melting point polylactic acid component comes from: The polylactic acid resin model is LX930, with a melt index of 18g / 10min (210℃ / 2.16kg); the high melting point polylactic acid component comes from, The polylactic acid resin model LX130 has a melt index of 23g / 10min (210°C / 2.16kg), which makes the water content of the high and low melting point polylactic acid chips reach 0.008-0.015%.
[0096] 2) The high and low melting point polylactic acid slices after drying are respectively sent to the twin screws of the composite twin-screw spinning machine for melt extrusion, wherein the screw extrusion temperature of the low melting point polylactic acid component is 180°C, and the screw extrusion temperature of the high melting point polylactic acid component is 210°C; after metering and filtration, they are sent to the composite spinning assembly of the spinning machine, and the volume ratio of the high and low melting point polylactic acid components is 70:30. Due to the large difference in melting points of the high and low melting point polylactic acid components, in order to avoid the phenomenon of broken ends and injected ends during the spinning process, the successful spinning parameters are: the spinning temperature is controlled at (230°C), and the spinning speed is controlled at 800m / min , the side blowing temperature is controlled at 22℃, the side blowing speed is controlled at 1m / s, the pre-drawing multiple is controlled at (1.5), and then after oiling treatment, a secondary oiling process is adopted, one oiling adopts the oil bath oiling method, and the short fiber oil agent of Japan Takemoto Oil Company is adopted, the model is 6214-TS, and the oiling rate is controlled at 0.2%. Then it enters the stretching process, and the stretching multiple is controlled at (1.8), and then tensile heat setting is carried out, and the heat setting temperature is controlled at (60℃)℃, and then the secondary oiling is carried out, and the oil is applied by oil tanker or spraying, and the multiple hydrophilic oil agent Lurol of Goulston Company is adopted. PP-14160, the oiling rate is controlled at 0.15%, enters the secondary heat setting, the temperature is controlled at (100°C), and then it is wound and cut to obtain a high and low melting point two-component polylactic acid composite fiber with a cross-shaped cross-section. The fiber fineness is 3.5dtex, the number of curls is 4 / 2.5mm, the curl angle is 100, the cross aspect ratio of the composite fiber is 5:1, and the fiber length is 5mm.
[0097] The degradable absorbent core involved in this embodiment includes the polylactic acid two-component composite fiber; the degradable absorbent core includes a surface layer 10, a middle layer 20 and a bottom layer 30; the surface layer 10 and the bottom layer 30 are single-component polylactic acid fiber non-woven fabrics; the middle layer includes polylactic acid two-component composite fibers with a cross cross-section, highly curled and highly elastic polylactic acid two-component fibers and a highly absorbent resin.
[0098] In the process of preparing the degradable absorbent core, the materials used are: prepared cross-shaped polylactic acid bicomponent fiber, high-curl and high-elastic polylactic acid bicomponent fiber and polylactic acid fiber non-woven fabric, among which the polylactic acid fiber non-woven fabric is preferably polylactic acid spunbond non-woven fabric. The high-curl polylactic acid bicomponent fiber is a degradable high-curl fiber with a parallel cross-section specially developed by Suzhou Jinquan New Materials Co., Ltd., in which one of the low-viscosity components is Polylactic acid resin model LX530, melt index is 23g / 10min (210℃ / 2.16kg); high viscosity component polylactic acid comes from The polylactic acid resin model is LX175, and the melt index is 6g / 10min (210℃ / 2.16kg). The fineness of the high-curl polylactic acid two-component fiber is 1.5dtex, the number of crimps is 8 / 2.5mm, and the fiber length is 10mm.
[0099] Fiber mixing: A three-dimensional motion mixer is used to mix the cross-type polylactic acid bicomponent fiber and the high-curl high-elasticity polylactic acid bicomponent fiber, and the ratio of the cross-type polylactic acid bicomponent fiber to the high-curl high-elasticity polylactic acid bicomponent fiber is 70:30.
[0100] In the process of preparing the degradable absorbent core, a non-woven fabric compounding machine with three spray heads, produced by Jiangsu Gaoqi Machinery Co., Ltd., model GQ-1600, was selected. The preparation process of the degradable absorbent core is as follows:
[0101] 1) Preparation before compounding: adjust the height between the first spray head and the compound machine surface to 12cm, the height between the second spray head and the compound machine surface to 13cm, and the height between the third spray head and the compound machine surface to 15cm.
[0102] 2) Unwind the polylactic acid spunbonded nonwoven fabric and send it to a nonwoven fabric laminating machine for lamination. The polylactic acid spunbonded nonwoven fabric with a specification of 18 g / m2 is selected.
[0103] 3) When the polylactic acid spunbond nonwoven fabric runs to the first powder sprinkling head, the first powder sprinkling head sprays a mixture of cross-shaped polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber and super absorbent resin on it. The selected ratio is cross-shaped polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber: super absorbent resin: 1:9, the spraying amount is 140 g / m2, and the vibration frequency of the first spraying head during spraying is 30 Hz.
[0104] 4) When the polylactic acid spunbond nonwoven fabric runs to the second powder sprinkling head, the second powder sprinkling head sprays a mixture of cross-type polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber and super absorbent resin on it. The selected ratio is cross-type polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber: super absorbent resin: 5:5, the spraying amount is 80 g / m2, and the vibration frequency of the second spraying head during spraying is 38 Hz.
[0105] 5) When the polylactic acid spunbond nonwoven fabric runs to the third powder sprinkling head, the third powder sprinkling head sprays a mixture of cross-type polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber and super absorbent resin on it. The selected ratio is cross-type polylactic acid bicomponent fiber + high-curl high-elastic polylactic acid bicomponent fiber: super absorbent resin: 8:2, the spraying amount is 50 g / m2, and the vibration frequency of the third spraying head during spraying is 45 Hz.
[0106] 6) Polylactic acid hot air nonwoven fabric is unwound (the specification of polylactic acid hot air nonwoven fabric is 18g / m2), and it is superimposed on the top layer of cross-shaped polylactic acid bicomponent fiber + high curl high elastic polylactic acid bicomponent fiber and super absorbent resin mixture to form a polylactic acid spunbond nonwoven fabric at the bottom layer, three layers of cross-shaped polylactic acid bicomponent fiber + high curl high elastic polylactic acid bicomponent fiber and super absorbent resin mixture in the middle, and a five-layer composite structure of polylactic acid hot air nonwoven fabric on the top layer. The composite structure is then put into the oven for shaping treatment. The hot air penetration temperature in the oven is 130°C, and the operating speed is 17 meters / minute. After leaving the oven, a five-layer composite absorbent material is obtained with a gram weight of 306 grams / square meter. The core can be used for the absorption layer of disposable sanitary materials such as diapers, sanitary napkins and nursing pads.
[0107] The following performance tests were performed on the embodiments, including:
[0108] (1) Absorption rate
[0109] The test steps for absorption speed are:
[0110] Prepare physiological saline with a concentration of 0.9% (simulating artificial urine), cut the composite absorbent material prepared by the present invention into strips with a width of 95 mm, flatten and straighten them, place a standard national standard funnel at the midpoint of the composite absorbent material, adjust the height of the funnel so that the lower end of its lower opening is 5-10 mm away from the surface of the test sample, measure 80 ml of physiological saline with a measuring cylinder, pour it into the liquid discharge funnel, and then quickly open the funnel valve to the maximum to allow the solution to flow freely to the surface of the sample, and at the same time count, and stop the timing after the liquid completely penetrates below the surface layer. The recorded time is the absorption rate of the test sample.
[0111] (2) Diffusion length and re-infiltration volume
[0112] Diffusion length: Take 0.9% saline (simulating artificial urine) as the test solution, pour it into the funnel, and after balance, quickly open the funnel valve to the maximum, so that the liquid can flow freely to the surface of the sample and start timing. After 5 minutes, inject the same amount of saline again. After 9 minutes, use a steel ruler to measure the diffusion length of the liquid in the absorbent material. Diffusion length = the average of the maximum and minimum lengths of the liquid after two injections
[0113] Re-seepage volume: Tested according to Appendix A of GB / T 28004-2011
[0114] (3) Saturation absorption
[0115] Given the wet weight of the nylon bag A and the weight after drying B, cut a 0.5m long piece of the absorbent material to be tested and weigh it, record it as C, put the absorbent material to be tested into the nylon bag, immerse it completely in 0.9% saline solution for 30 minutes, take it out and hang it on the drain rack, and after 10 minutes, weigh the absorbent material to be tested and the nylon bag as a whole, record it as D. Saturated absorption capacity = DAC.
[0116] (4) pH value
[0117] Tested according to the method specified in Appendix C of GB / T 8939-2008.
[0118] (5) Degradability
[0119] The test was carried out according to the method of GB / T19277-2003 (IDT ISO 14855:1999).
[0120] The test results are shown in Table 1.
[0121] Table 1: Test results of composite absorbent material performance
[0122]
[0123] The results of the degradation test of the absorbent core material of the present invention are shown in Table 2
[0124] Table 2: Degradation test results
[0125]
[0126] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A polylactic acid two-component composite fiber, characterized in that: It comprises a core with a cross-shaped cross section and a skin covering the outside of the core layer and having a cross-shaped cross section; the core is made of high-melting-point polylactic acid, and the skin is made of low-melting-point polylactic acid; The preparation process of the polylactic acid two-component composite fiber is as follows: 1) First, the high melting point polylactic acid slices and the low melting point polylactic acid slices are dried by a drying device until the water content of the high melting point polylactic acid slices and the low melting point polylactic acid slices is 0.008-0.015%; 2) The dried high-melting-point polylactic acid slices and low-melting-point polylactic acid slices are respectively sent to the twin screws of a composite twin-screw spinning machine for melt extrusion; the screw extrusion temperature of the low-melting-point polylactic acid component is 170-190° C., and the screw extrusion temperature of the high-melting-point polylactic acid component is 200-230° C.; after being metered and filtered, they are sent to the composite spinning assembly of the spinning machine; The spinning parameters are as follows: the spinning temperature is controlled at 215-245°C, the spinning speed is controlled at 600-1000m / min, the side blowing temperature is controlled at 20-24°C, the side blowing speed is controlled at 0.8-1.2m / s, the pre-drafting multiple is controlled at 1.3-1.8, and then after oiling treatment, a secondary oiling process is adopted; the first oiling adopts an oil bath oiling method, and the oiling rate is controlled at 0.18-0.25%, and then enters the stretching process, the stretching multiple is controlled at 1.5-2.0, and then tensile heat setting is carried out, the heat setting temperature is controlled at 55-65°C, and then the second oiling is carried out, the oiling is carried out by an oil tanker or a spraying method, the oiling rate is controlled at 0.1-0.2%, and then enters the secondary heat setting method, the temperature is controlled at 90-110°C, and then winding and cutting are performed to obtain a high-low melting point two-component polylactic acid composite fiber with a cross-shaped cross section.
2. The polylactic acid two-component composite fiber according to claim 1, characterized in that: The drying equipment is a rotary drum drying equipment; the low melting point polylactic acid component has a melting index of 18 g / 10 min; the high melting point polylactic acid component has a melting index of 23 g / 10 min.
3. The polylactic acid two-component composite fiber according to claim 1, characterized in that: The fiber fineness of the polylactic acid two-component composite fiber is 1.5-6 dtex, the number of curls is 2-5 / 2.5 mm, and the curl angle is 80-100 degrees; the cross aspect ratio of the polylactic acid two-component composite fiber is 3-7:1, and the fiber length is 3-20 mm.
4. The polylactic acid two-component composite fiber according to claim 1, characterized in that: The volume ratio of the high melting point polylactic acid slices to the low melting point polylactic acid component is 60-80:20-40.
5. A degradable absorbent core, characterized in that: The polylactic acid two-component composite fiber comprises the polylactic acid two-component composite fiber according to claim 1; The degradable absorbent core comprises a surface layer, a middle layer and a bottom layer; the surface layer and the bottom layer are single-component polylactic acid fiber non-woven fabrics; the middle layer comprises polylactic acid two-component composite fibers with a cross section, highly curled and highly elastic polylactic acid two-component fibers and highly absorbent resin.
6. A degradable absorbent core according to claim 5, characterized in that: The high-curl and high-elastic polylactic acid two-component fiber is in a parallel type, including a low melting point component and a high viscosity component, the melt index of the low viscosity component is 23g / 10min, and the melt index of the high viscosity component is 6g / 10min; the fiber fineness of the high-curl and high-elastic polylactic acid two-component fiber is 1.5-6dtex, the number of curls is 8-12 / 2.5mm, and the fiber length is 10-25mm.
7. The degradable absorbent core according to claim 5, characterized in that: The preparation process of the intermediate layer is as follows: 1) Fiber mixing: mixing the cross-sectioned polylactic acid two-component composite fiber and the high-curl high-elasticity polylactic acid two-component fiber to form a fiber mixture; 2) Mixing: Mixing the fiber mixture with the super absorbent resin to prepare a first fiber resin mixture, a second fiber resin mixture and a third fiber resin mixture; The ratio of fiber mixture to super absorbent resin in the first fiber resin mixture is 0-2:8-10, wherein the particle size of the super absorbent resin used is 100-120 mesh; The ratio of fiber mixture to super absorbent resin in the second fiber resin mixture is 4-6:4-6, wherein the particle size of the super absorbent resin used is 80-100 mesh; The ratio of fiber mixture to super absorbent resin in the third fiber resin mixture is 7-9:1-3, wherein the particle size of the super absorbent resin used is 40-70 meshes.
8. The degradable absorbent core according to claim 7, characterized in that: The mixing ratio of the polylactic acid two-component composite fiber and the high-curl high-elasticity polylactic acid two-component fiber is 50-70:50-30.
9. The degradable absorbent core according to claim 7, characterized in that: The preparation process of the degradable absorbent core adopts a non-woven fabric compounding machine with three spray heads, and the specific preparation process is as follows: 1) Preparation before compounding: adjust the height between the first spray head and the compound machine table to 10-13 cm, adjust the height between the second spray head and the compound machine table to 12-14 cm, and adjust the height between the third spray head and the compound machine table to 13-15 cm; 2) unwinding the polylactic acid spunbonded nonwoven fabric used for the bottom layer and sending it to a nonwoven fabric laminating machine for lamination, wherein the polylactic acid spunbonded nonwoven fabric with a specification of 15-20 g / m2 is selected; 3) When the polylactic acid spunbond nonwoven fabric runs to the first powder spraying head, the first powder spraying head sprays the first fiber resin mixture thereon, the spraying amount is 120-180 g / m2, and the vibration frequency of the first spraying head during spraying is 20-30 Hz; 4) When the polylactic acid spunbonded nonwoven fabric runs to the second powder sprinkling head, the second powder sprinkling head sprays the second fiber resin mixture thereon, the spraying amount is 60-100 g / m2, and the vibration frequency of the second spraying head during spraying is 28-38 Hz; 5) When the polylactic acid spunbonded nonwoven fabric runs to the third powder spraying head, the third powder spraying head sprays the third fiber resin mixture thereon, the spraying amount is 40-70 g / m2, and the vibration frequency of the third spraying head during spraying is 35-45 Hz; 6) unwinding the polylactic acid hot air nonwoven fabric used for the surface layer, and superimposing it on the sprayed third fiber resin mixture, so that the polylactic acid spunbond nonwoven fabric is at the bottom layer, the middle layer is a three-layer cross-shaped polylactic acid bicomponent fiber + a high-curl high-elasticity polylactic acid bicomponent fiber superabsorbent resin mixture, and the upper layer is a five-layer composite structure of polylactic acid hot air nonwoven fabric; The composite structure is then put into an oven for shaping. The hot air penetration temperature in the oven is 115-140°C and the running speed is 15-20 m / min. After exiting the oven, a five-layer composite absorbent material is obtained with a gram weight of 300-460 g / m2.
Citation Information
Patent Citations
Degradable composite absorption core, preparation method thereof and application thereof in paper diapers
CN111920587A
Preparation method of environment-friendly composite fiber for hygienic materials
CN113355756A
Preparation process of composite absorption core body for paper diaper
CN114099146A
Biodegradable sanitary towel with polylactic acid as main component
CN119280452A
Biodegradable paper diaper
CN119280453A